Die noodsaaklikheid van onderrig- ontwikkeling aan die Universiteit - Plessis, S. J. P. du (Koers, 1983)
As a result of a shortage of skilled manpower, the rapid increase in knowledge and technological development, personnel development has become an issue of great and urgent necessity. In this article the author looks at the necessity of leaching development as an important component of the development and promotion of lecturing at the university, and comes to the conclusion that lecturers at tertiary (university) level need to be made cognizant of recent developments in the techniques of tertiary teaching so that leaching can be as effective as possible in an effort to render more effective service to the community served by the university.